I Like the Food You Made! Overly Positive Feedback Is Most Likely Given to Those That Want to Excel in a Task and Handle Failure Badly - Cantarero, Katarzyna; Byrka, Katarzyna; Kosiarczyk, Aleksandra; Dolinski, Dariusz (Frontiers in Psychology, 2022)
In this article, we focus on how people resolve the dilemma between honest feedback and a prosocial lie depending on the context. In a pre-registered study (N = 455), we asked participants to choose between telling the blatant truth or lying prosocially regarding a dish made poorly by a stranger. The results showed that participants were most eager to pass on overly positive feedback when the stranger cared about cooking and was very sensitive to negative feedback. Perceived harm in truth telling mediated the relationship between desire to excel in a task with high ability to handle failure and choosing a prosocial lie.